IPTEKS PROSEDUR PERTANGGUNGJAWABAN BIAYA PERJALANAN DINAS PADA BIRO UMUM DAN PROTOKOL SEKRETARIAT DAERAH PROVINSI SULAWESI UTARA - Rompas, Ferdinand Vikky; Rundengan, Fanda D.P (Universitas Sam Ratulangi, 2018)
The government must run the wheels of government honestly and cleanly and its neighbors must comply with the applicable laws and regulations. In managing finances the government must be able to account for every rupiah spent in carrying out government duties. The corruption cases of Official Travel have been many because of those who were not responsible. Regulations concerning Official Travel in the PMK Number 113 of 2012 concerning domestic official travel for State officials, civil servants and temporary employees. The purpose of this study is to find out whether the Accountability of Travel Agency Services at the General Bureau and Protocol of the Regional Secretariat of North Sulawesi Province is in accordance with the PMK Number 113 of 2012Â concerning domestic official travel for State officials, civil servants, and the employee is not permanent or not. The results of the study show that the Accountability of Travel Agency Services at the General Bureau and Protocol of the Regional Secretariat of North Sulawesi Province is in accordance with the PMK Number 113 of 2012.Keywords: government, accountability, official travel costs.